PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN MELALUI MICROSOFT TEAMS TERHADAP HASIL BELAJAR PENGOLAHAN AUDIO VIDEO - Ignatius Satriya Bagus Pradana; Yuliana Tien Bayangkhariwati Tacoh (Jurnal Education and Development, 2021)
This study aims to determine the effect of using video media in online learning through Microsoft Teams on student learning outcomes in Audio Video Processing subjects at Pringapus Vocational School. This study uses a quasi-experimental. The population of this research is students of XII Multimedia SMKN 1 Pringapus. The research sample is the experimental class XII MM.2 and the control class is the control class XII MM.3 sample. The research instrument was in the form of a test given during the Pre-test and Post-Test. Data analysis used the t-test formula. From the research data, the t value is 3.153 > t table 2.00172 and the Sig. (2-tailed) value is 0.03 < from 0.05. The results showed that there was a significant difference between the results of the Post-Test experimental class and the control class, it can be concluded that there is a significant effect of using learning videos through Microsoft Teams on student learning outcomes in Audio Video Processing subjects.